Management of Educational Facilities and Infrastructure in Developing the Quality of Islamic Religious Education at MTs Swasta Sabila Hamparan Perak - Tanjung, Jihad; Maisyara, Siti; Elysa, Elysa; Setiawan, Hasrian Rudi (Integrasi: Jurnal Studi Islam dan Humaniora, 2024)
Infrastructure is a tool that supports the learning process provided by the school. School infrastructure is one part that must be paid attention to by all levels of society. Without the infrastructure, learning cannot run optimally. The motive for this research is to understand how educational facilities and infrastructure are managed in the development of PAI education at the Sabila Hamparan Perak Private MTs. This type of research is qualitative research using a descriptive approach. Data collection techniques through interviews, observation and documentation. The results of this research are that there are many differences between other schools and the Sabila Hamparan Perak Private MTs school in terms of facilities and infrastructure. The difference lies in terms of completeness. The infrastructure at the Sabila Hamparan Perak Private MTs is very limited, but students still have to take part in learning. But this does not become an obstacle to student learning. Sabila Hamparan Perak Private MTs is famous for being a school that has just been established, and also the number of students is still small, which is an important point. Because the small number of students will make the teacher more focused on teaching. Apart from that, students can be encouraged and accustomed to doing things as optimally as possible and invited to take part in various competitions that suit their talents and interests. Apart from that, students are stimulated to have future goals and so that they can focus on these goals.